Reduplikasi Bahasa Batak Toba di Desa Tengganau Kecamatan Pinggir Kabupaten Bengkalis - Yanti, Yuli; Alber, Alber (UIR Press, 2023)
This research is motivated by the Batak Toba language in Tengganau Village, Pinggir District, Bengkalis Regency which is used every day by the community when communicating in the form and meaning of reduplication aspects. The focus of this research is the form and meaning of the reduplication of the Toba Batak language in Tengganau Village. This research aims to describe the forms of reduplication of the Toba Batak language in Tengganau Village, Pinggir District, Bengkalis Regency and analyze the meaning of the reduplication of the Toba Batak Language in Tengganau Village, Pinggir District, Bengkalis Regency. The theory used in this research is Ramlan. The approach used in this study is a qualitative approach. This research method is a descriptive research method. Data collection techniques in this research include interviews, recording (audio), fishing and notes. The conclusion of this research is to form language speakers who have knowledge and skills so that the author knows the form of Toba Batak language reduplication in Tengganau Village, Pinggir District, Bengkalis Regency. This research has implications for teaching Indonesian language learning. The results of the research can be used by teachers in the field of Indonesian language studies as teaching material, especially in the fields of morphology and semantics. In addition, this research provides information to teachers and students about reduplication or rewording. This research can later be used as teaching material in Indonesian language subject matter, namely reduplication. The more students understand the reduplication material with the teaching materials, the higher the students' appreciation of the language.